S‐wave splitting in the offshore South Island, New Zealand: Insights into plate‐boundary deformation. (30th August 2015) - Karalliyadda, S. C.; Savage, M. K.; Sheehan, A.; Collins, J.; Zietlow, D.; Shelley, A.
Abstract Local and regional S‐wave splitting in the offshore South Island of the New Zealand plate‐boundary zone provides constraints on the spatial and depth extent of the anisotropic structure with an enhanced resolution relative to land‐based and SKS studies. The combined analysis of offshore and land measurements using splitting tomography suggests plate‐boundary shear dominates in the central and northern South Island. The width of this shear zone in the central South Island is about 200 km, but is complicated by stress‐controlled anisotropy at shallow levels. In northern South Island, a broader (>200 km) zone of plate‐boundary parallel anisotropy is associated with the transitional faulting between the Alpine fault and Hikurangi subduction and the Hikurangi subduction zone itself. These results suggest S‐phases of deep events (∼90 km) in the central South Island are sensitive to plate‐boundary derived NE‐SW aligned anisotropic media in the upper‐lithosphere, supporting a "thin viscous sheet" deformation model.